S117 Poor adherence in exacerbating COPD patients: magnitude and related factors at baseline in the MAGNIFY pragmatic trial. (11th November 2022) - Dickens, AP; Halpin, DMG; Carter, V; Skinner, D; Beeh, K; Chalmers, J; Clark, A; Hannan, N; Kaplan, A; Kostikas, K; Pinnock, H; Roche, N; et al.
Abstract : Introduction and Objectives: Maintenance inhaled therapies can stabilise COPD symptoms and reduce the risk of exacerbations, but inhaler adherence is often poor. Patients experiencing frequent exacerbations represent a specific high-risk population in need of further intervention. Little data exist regarding inhaled medication adherence amongst exacerbating COPD patients. The MAGNIFY cluster randomised trial is investigating the effect of a technologically-supported adherence package for exacerbating COPD patients in primary care. Using baseline data from this trial, we explore inhaler adherence and compare characteristics of exacerbating COPD patients, stratified by adherence to inhaled maintenance therapy. Methods: Algorithms run on electronic medical records (EMR) of 137 GP practices identified COPD patients aged ≥40 years, with ≥2 moderate/severe exacerbations in the last two years. EMR-based patient adherence was based on the 12 months prior to 1st March 2020, if ever prescribed inhaled maintenance therapy. Results: Of those with available data, 41.2% of COPD patients (10882/26411) had ≥2 moderate/severe exacerbations in the last two years. Almost two thirds (6929/10882, 63.7%) of the patient sample were prescribed triple therapy, with LABA/ICS being the second most common therapy (1699/10882, 15.6%) ( table 1 ). Over a third of patients (4168/10882, 38.3%) were ≤50% adherent on at least one therapy. Patients with ≤50% adherence had more health care contacts in the 12 months prior to 1st March 2022, worse dyspnoea and inhaler technique, and proportionally higher prescriptions for triple therapy. Furthermore, patients on triple therapy were more likely to have ≤50% adherence compared to any other therapy type (43.5% vs 31.4% or lower). Conclusions: Poor adherence was common amongst exacerbating COPD patients, and was associated with more health care contacts, and worse respiratory symptoms and inhaler technique. Triple therapy was the most common inhaled maintenance therapy in this patient population, but it also had substantially lower adherence compared to other therapies. Adherence was worse amongst patients on dual and triple therapies, indicating that future adherence support interventions should be targeted at these subgroups. Analyses comparing adherence to open/closed inhaled therapies will be presented at the conference.